Analisis Pengaruh Jarak dan Beban terhadap Konsumsi Daya Motor BLDC 2000 Watt pada Prototipe Sepeda Listrik E-Bomber - Fitra Abu Rizal; Azam Muzakhim Imammuddin (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Air pollution and oil reserves are two major issues in the technological development of the automotive industry. Air pollution is caused by gases from burning fossil fuel vehicles. In 2018-2019 Indonesia experienced a drastic decrease in petroleum resources by 49.8%. To overcome this problem, many researchers have conducted research on electric vehicles, including electric bicycles. This study aims to determine the effect of distance and load on BLDC motor power consumption on a prototype e-bomber electric bicycle designed for all terrains such as rocky, sandy, and muddy, and has a large battery capacity, low power consumption, and an electric motor with good speed and torque. This research uses a pseudo-experimental method with a quantitative approach. Tests were carried out on e-bomber electric bicycles with distances of 3 km, 5 km, and 8 km and loads of 60 kg, 70 kg, and 80 kg with a speed of 25 km / h. The results showed that there was an influence of distance and load on the e-bomber electric bicycle. The results showed that there was an effect of distance and load on BLDC motor power consumption with the results of graph analysis and two-way ANOVA tests conducted and the lowest average power consumption of 500 watts at a distance of 3 km and a load of 60 kg, while the highest average power consumption was 522.5 watts at a distance of 8 km and a load of 80 kg.